Association between genetic mutations and risk of venous thromboembolism in patients with solid tumor malignancies: A systematic review and meta-analysis. Issue 213 (May 2022) - Abufarhaneh, Mohammed; Pandya, Rudra Kashyap; Alkhaja, Ahmed; Iansavichene, Alla; Welch, Stephen; Lazo-Langner, Alejandro
Abstract: Background: Venous thromboembolism (VTE) is a frequent complication in cancer patients and is associated with significant morbidity, mortality, and burden on the health care system [1] . Previous studies have suggested an association between genetic mutations in solid tumors and VTE risk. Methods: MEDLINE and EMBASE databases were searched from inception to February 2021. We aimed to include studies presenting data on VTE and genetic mutations with >5% frequency in patients with melanoma, small cell lung cancer (SCLC), non-small cell lung cancer (NSCLC), and colon, gastric and ovarian cancers. Meta-analyses of proportions and size effects were conducted if possible. Results: Of 682 eligible articles, we included 33 articles, of which 26 papers reporting on a total of 13, 844 patients were included in the meta-analysis. The estimated proportions of VTE in lung cancer patients with EGFR, KRAS, and ALK mutations were 7.3, 18.2, and 30.6%, respectively, whereas for colon cancer with KRAS mutations was 13%. In NSCLC patients with EGFR, KRAS and ALK mutations the relative risk (RR) of VTE was 0.98 (0.81–1.18, P = 0.818), 1.24 (0.78–1.97 P = 0.358) and 1.70 (1.46–1.97, P < 0.001), respectively using a fixed-effects model. In patients with colon cancer and KRAS mutation, no significant increase in the VTE risk was observed according to the random-effects model, RR 1.31 (0.79–2.19, P = 0.285). Conclusion: In patients with NSCLC, the presence of ALK mutations was associated with a high proportion and RR of developing VTE. There was no significant increase in the risk of VTE in patients with colon cancer and KRAS mutations.